Role of Vascular Networks in Extending Glucose Sensor Function: Impact of Angiogenesis and Lymphangiogenesis on Continuous Glucose Monitoring in vivo - Klueh, Ulrike (2013)
The concept of increased blood vessel (BV) density proximal to glucose sensors implanted in the interstitial tissue increases the accuracy and lifespan of sensors is accepted, despite limited existing experimental data. Interestingly, there is no previous data or even conjecture in the literature on the role of lymphatic vessels (LV) alone, or in combination with BV, in enhancing continuous glucose monitoring (CGM) in vivo. To investigate the impact of inducing vascular networks (BV and LV) at sites of glucose sensor implantation, we utilized adenovirus based local gene therapy of vascular endothelial cell growth factor-A (VEGF-A) to induce vessels at sensor implantation sites. The results of these studies demonstrated that 1) VEGF-A based local gene therapy increases vascular networks (blood vessels and lymphatic vessels) at sites of glucose sensor implantation; and 2) this local increase of vascular networks enhances glucose sensor function in vivo from 7 days to greater than 28 days post sensor implantation. This data provides “proof of concept” for the effective usage of local angiogenic factor (AF) gene therapy in mammalian models in an effort to extend CGM in vivo. It also supports the practice of a variety of viral and non-viral vectors as well as gene products (e.g. anti-inflammatory and anti-fibrosis genes) to engineer “implant friendly tissues” for the usage with implantable glucose sensors as well as other implantable devices.